Glutamate receptor and transporter modifications in rat organotypic hippocampal slice cultures exposed to oxygen–glucose deprivation: The contribution of cyclooxygenase-2. (30th April 2015) - Llorente, I.L.; Landucci, E.; Pellegrini-Giampietro, D.E.; Fernández-López, A.
Graphical abstract: Highlights: Meloxicam reduces CA1 mortality induced by 30 min of OGD in the organotypic hippocampal cell culture model. Meloxicam lessens the OGD-induced increases or decreases in GluN1-2, GluA1, VGLUT1, GLAST-1A, GLT-1 and EEAC-1 transcripts. GluN2B, GluA2 and VGLUT2 transcript levels are strongly increased during OGD in the presence of meloxicam. The two OGD-induced transcript level response patterns observed in the presence of meloxicam are lost 24 h after OGD. Protein level changes have not been detected by OGD or the presence of meloxicam at the times studied. Abstract: Meloxicam is a non-steroidal anti-inflammatory drug which has been reported to lessen the ischemic transcriptional effects in some of the glutamatergic system genes as well as to decrease the infarct volume in in vivo assays. In this study, we show how the presence of meloxicam decreases cell mortality in assays of oxygen–glucose deprivation (OGD) in rat organotypic hippocampal slices culture. Mortality was measured using propidium iodide. Transcript levels of some glutamatergic system genes, including vesicular and membrane glutamate transporters (VGLUT1, VGLUT2, GLAST-1A, GLT-1, and EAAC-1) and some glutamatergic receptor subunits (NMDA receptor, GluN1, GluN2A and GluN2B subunits and AMPA receptor, GluA1 and GluA2 subunits) were measured by real-time PCR (qPCR). The transcription of vesicular glutamate transporters and glutamatergic receptor subunits, but not membrane glutamate transporters, was modified by the presence of meloxicam. The study demonstrates the neuroprotective role of meloxicam in organotypic hippocampal slice cultures and shows how meloxicam is able to selectively increase or decrease the OGD-induced changes in the expression of the different glutamatergic system genes studied here. We suggest that the neuroprotective role of meloxicam could be due to a modification in the balance of the expression of some glutamatergic receptor subunits, leading to a different stoichiometry of receptors such as NMDA or AMPA. Thus, meloxicam would decrease the excitotoxicity induced by OGD.